Dietary High‐Oleic Acid Soybean Oil Dose Dependently Attenuates Egg Yolk Content of n‐3 Polyunsaturated Fatty Acids in Laying Hens Fed Supplemental Flaxseed Oil. Issue 2 (22nd March 2018) - Elkin, Robert G.; Kukorowski, Alexandra N.; Ying, Yun; Harvatine, Kevin J.
Abstract: Chickens can hepatically synthesize eicosapentaenoic acid (20:5 n‐3) and docosahexaenoic acid (22:6 n‐3) from α‐linolenic acid (ALA; 18:3 n‐3); however, the process is inefficient and competitively inhibited by dietary linoleic acid (LNA; 18:2 n‐6). In the present study, the influence of dietary high‐oleic acid (OLA; 18:1 n‐9) soybean oil (HOSO) on egg and tissue deposition of ALA and n‐3 polyunsaturated fatty acids (PUFA) synthesized from dietary ALA was investigated in laying hens fed a reduced‐LNA base diet supplemented with high‐ALA flaxseed oil (FLAX). We hypothesized that reducing the dietary level of LNA would promote greater hepatic conversion of ALA to very long‐chain (VLC; >20C) n‐3 PUFA, while supplemental dietary HOSO would simultaneously further enrich eggs with OLA without influencing egg n‐3 PUFA contents. Nine 51‐week‐old hens each were fed 0, 10, 20, or 40 g HOSO/kg diet for 12 weeks. Within each group, supplemental dietary FLAX was increased every 3 weeks from 0 to 10 to 20 to 40 g/kg diet. Compared to controls, dietary FLAX maximally enriched the total n‐3 and VLC n‐3 PUFA contents in egg yolk by 9.4‐fold and 2.2‐fold, respectively, while feeding hens 40 g HOSO/kg diet maximally attenuated the yolk deposition of ALA, VLC n‐3 PUFA, and total n‐3 PUFA by 37, 15, and 32%, respectively. These results suggest that dietary OLA is not neutral with regard to the overall process by which dietary ALA is absorbed, metabolized, and deposited into egg yolk, either intact or in the form of longer‐chain/more unsaturated n‐3 PUFA derivatives.